IMPLEMENTASI METODE K-NEAREST NEIGHBOUR DALAM MEMPREDIKSI CURAH HUJAN DI KOTA BOGOR - Naufal Rasyid; Trevy Jonatya Novella; Ahlijati Nuraminah (JURAL RISET RUMPUN ILMU TEKNIK, 2022)
Accurate weather prediction information is important for various fields that are closely related to weather forecasting, such as agriculture, fisheries and many more. Because precise weather forecasts are very useful for various fields of carrying out various activities. Because of that, it is necessary to make an application to find weather or rainfall prediction information, so that the information can be utilized optimally by the community. In this journal the authors apply the k-nearest neighbors (k-NN) method based on rainfall data obtained from the Bogor climatology station from 2016-2017 and the test results show that the predicted rainfall for the Bogor area with the K-Nearest Neighbor algorithm obtained a value of 0, 93148.